ANALISIS KEAMANAN JARINGAN DENGAN METODE SECURITY LIFECYCLE DI UNIVERSITAS IBN KHALDUN BOGOR - Hendrawan, Ade Hendri; Setiawan, Foni Agus; Mulyo, Arief Sekto (Krea-TIF: Jurnal Teknik Informatika, 2014)
Computer network located in the building of Faculty of Engineering, Universitas Ibn Khaldun Bogor (FT UIKA) is currently the center of internet facility provider and Academic and Financial Information System (SIAK) which is connected directly to the Rectorat building. All services either internet connection and applications accessed by the faculties of UIKA have to go through this pathway. This strategic role of the network in FT UIKA need reliable security that are not easily damaged. One method of analyzing network security is Security Lifecycle (SLC). This method has stages ranging from data analysis of potential threats that may occur, the policy on what is allowed and not allowed to run a system, and specification of the desired system functionality, as well as the results of implementation of the security system tested. This study conducted a security analysis of UIKA network using SLC, build fortifications against attacks, perform a series of tests, and recommend matters related to network security and services in the FT UIKA. Implementation of these recommendations on computer network in UIKA will secure the system from various types of attacks to keep the continuity of operations.